2013
DOI: 10.1017/s0014479713000148
|View full text |Cite
|
Sign up to set email alerts
|

PHOTOSYNTHETIC CHARACTERISTICS AND FIBRE PRODUCTION FOLLOWING DEFOLIATION INATTALEA FUNIFERAMART., ARECACEAE, GROWING UNDER FULL SUN AND FOREST UNDERSTOREY

Abstract: SUMMARYThe effects of leaves cut during fibre harvesting of Attalea funifera under contrasting irradiance availability were evaluated, studying defoliation-induced changes in photosynthetic and growth characteristics and fibre production in adult individuals of A. funifera growing under full sun and forest understorey. Fibre harvesting was performed with or without (control plants) leaf removal twice in a 12-month interval. Maximum measured values of net photosynthesis (A), stomatal conductance and transpirati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
(51 reference statements)
1
4
0
1
Order By: Relevance
“…Only in H2 (in which solar radiation in the understory was higher than in H1) did harvesting stimulate the growth of small palms. This finding agrees with studies stating that only when solar radiation is high does the photosynthetic capability and relative growth rate of palms respond positively to defoliation [ 8 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Only in H2 (in which solar radiation in the understory was higher than in H1) did harvesting stimulate the growth of small palms. This finding agrees with studies stating that only when solar radiation is high does the photosynthetic capability and relative growth rate of palms respond positively to defoliation [ 8 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…With few exceptions, palms are highly tolerant to defoliation, and leaf production increases with harvesting intensity [ 5 , 25 , 32 , 36 ]. As a result, palms are able to compensate for the number of leaves extracted, although that capacity is reduced under low light intensity [ 8 , 17 , 33 ]. Both species of Sabal fit this general pattern: leaf production increased with harvest intensity, in most cases even overcompensating for the loss of leaves.…”
Section: Discussionmentioning
confidence: 99%
“…aculeata is similar to other studies, where intensely harvested individuals allocated more resources to vegetative structures and growth and less to reproductive structures [ 14 ]. In addition, if this harvest continues chronically, the negative effects on reproduction may be long, taking years to recover; as has been found for other palms [ 8 ], [ 10 ], [ 19 ], [ 49 ]. Additionally, because reproduction has a higher cost compared to vegetative costs, it is also expected to cause negative consequences on progeny [ 21 ], [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge most of the studies on leaf-harvesting have explored the effects from the physiological, phenological and/or morphological view [ 13 , 14 ], [ 46 ], [ 49 ]. Also, many have determined the effects on vegetative and reproductive traits, or the strategies of resource allocation between maintenance/growth/reproduction traits [ 7 ], [ 27 ], [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The persistence of S. mauritiiformis leaves in spite of the damage may be related to a slow metabolism in the low ambient light of the understory. In the palm Attalea funifera in Brazil, photosynthetic rates are consistently lower in the understory than under full sun exposure (Pamponet et al 2013). Leaf production in Geonoma schottiana is more limited by light availability than by soil humidity (Sampaio & Scariot 2008), and it has been experimentally shown that Euterpe edulis leaves increase their life span by 100 d in response to low light levels (Gatti et al 2011).…”
Section: Discussionmentioning
confidence: 99%